Decision Analysis for the Remanufacturing System in the Presence of Carbon Cap and Trade Policy and Low-Carbon Consumers - Xiaoge Meng; Shushu Xie; Menghao Xi; Yingxue Zhao (Discrete Dynamics in Nature and Society)
This paper considers a remanufacturing system in which an original equipment manufacturer (OEM) and an independent remanufacturer (IR) compete with each other. The paper conducts a model analysis for the optimal decisions in the remanufacturing system, taking into account the impacts of consumers’ low-carbon awareness and carbon cap and trade (CCT) policy. With the studies, it is found that the effects of CCT and consumers’ low-carbon awareness can be trading off sometimes on the remanufacturing system, and in this case, excessive cultivation of consumers’ low-carbon awareness will weaken the beneficial effects of CCT on the remanufacturing system due to the resulted excessive consumers’ willingness to pay for the remanufactured products.